Genetic variability through isozimic polymorphisms in hexaploid oats - Rodrigues Matiello, Rodrigo (1998)
Analysis of isozymes have many applications in plant breeding specially in the study of genetic variability. Isozymes are direct product of genic expression and may help to understand the evolutionary relation between species, and allow to identify the potential genotypes for breeding programs. This work aimed to identify genetic variability through esterase polymorphism and to estimate genetic similarity among three hexaploid oat groups. Nine cultivated oat genotypes, three introductions of A. sterilis L., and 16 introductions of A. fatua L. were used. Wide polymorphisms of isozyme were observed within and between studied groups. The electrophoretic analysis showed 13 different bands with anodical migration between the genotypes. Although several bands were common for all genotypes, some of them were typical for a particular hexaploid group. These results indicate high genetic similarity between cultivated oat and A. fatua group. The A. sterilis group was more divergent, due to a more differentiated electrophoretic pattern.